2000
DOI: 10.2134/jeq2000.00472425002900050031x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil Amendments on the Bioavailability of Lead, Zinc, and Cadmium to Earthworms

Abstract: This research investigated the effectiveness of phosphorus (P) and organic matter (OM) as possible in situ remediation techniques for metal contaminated soils. The study was designed to determine the bioavailability of Pb, Zn, and Cd individually and in combination to the earthworm Eisenia fetida in an artificial soil amended with varying levels of P and OM. A toxicokinetic approach using bioaccumulation factors and uptake rate coefficients was used to assess the bioavailability of the heavy metals. Overall, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 0 publications
1
34
0
4
Order By: Relevance
“…El proceso de vermicomposteo se llevó a cabo por triplicado y se utilizaron recipientes de plástico de 20 x 30 x 20 cm (ancho x largo x altura) como tinas de compostaje de acuerdo a lo reportado por Pearson et al (2000).…”
Section: Diseño Del Experimentounclassified
“…El proceso de vermicomposteo se llevó a cabo por triplicado y se utilizaron recipientes de plástico de 20 x 30 x 20 cm (ancho x largo x altura) como tinas de compostaje de acuerdo a lo reportado por Pearson et al (2000).…”
Section: Diseño Del Experimentounclassified
“…From Eqns 1 and 2 it can be seen that the two models had a high coefficient of determination (R 2 ) and a small standard error of the estimate (SE), which means the chemical transformation of Cd in calcareous soil treated with the two P-containing acidify agents was mainly associated with the addition level of P in water-soluble form and not soil pH. However, several studies have reported that water-soluble phosphate compounds can immobilise Cd through various mechanisms, such as surface complexation, ion exchange, precipitation and adsorption (LeviMinzi and Petruzzelli 1984;Pearson et al 2000;McGowen et al 2001;Bolan et al 2003;Thawornchaisit and Polprasert 2009). …”
Section: Chemical Transformation Of CDmentioning
confidence: 99%
“…Several laboratory and bench-scale remediation studies have demonstrated the effectiveness of the addition of phosphate-based soil amendments in producing highly insoluble lead phosphate minerals such as pyromorphite and hydroxypyromorphite (Berti and Cunningham 1997;Lambert et al 1997;Ma and Rao 1997;Lower et al 1998;Traina and Laperche 1999). When sequestered within these phosphate minerals, lead has been shown to be far less soluble, as indicated by the results of acid leaching tests (Tardy et al 2003), and its bioavailability to soil organisms has been demonstrated to be sharply reduced (Berti and Cunningham 1997;Pearson et al 2000;Traina and Laperche 1999). The USEPA has recognized that bioavailability of lead in contaminated soils varies greatly depending upon its form in the soil, and had suggested that phosphate treatment has potential for in-situ remediation of contaminated soils and sediments (USEPA 2001c).…”
Section: Prefacementioning
confidence: 99%